2008
DOI: 10.1108/14691930810913195
|View full text |Cite
|
Sign up to set email alerts
|

Censoring model for evaluating intellectual capital value drivers

Abstract: Purpose-The purpose of this paper is to examine the relationship between firms' value drivers and their intellectual capital (IC). Design/methodology/approach-The health care sector (GICS 35) firms listed in the S&P500 were used to build a research censoring Tobit model by adopting financial data to determine value drivers. Findings-The results of the study show that innovation capital, customer capital and human capital are significant positive drive factors for firms to create more IC and hence more intangib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Indictors of intellectual capital elements are collected from the literature on the measurement of intellectual capital or factors of business performance. By replacing the background information, such as age, education and work experience, we use average operating revenue per employee (Cheng et al, 2010;Tseng, et al, 2015) and average net profit per employee (Cheng et al, 2008) to stand for human capital because an increase in the revenue per employee means that the employees contribute more to the corporation and enhance the corporate value (Tseng et al, 2015).…”
Section: Datamentioning
confidence: 99%
“…Indictors of intellectual capital elements are collected from the literature on the measurement of intellectual capital or factors of business performance. By replacing the background information, such as age, education and work experience, we use average operating revenue per employee (Cheng et al, 2010;Tseng, et al, 2015) and average net profit per employee (Cheng et al, 2008) to stand for human capital because an increase in the revenue per employee means that the employees contribute more to the corporation and enhance the corporate value (Tseng et al, 2015).…”
Section: Datamentioning
confidence: 99%
“…An oft-cited study by Fornell (1992) found evidence that nurturing customer relationships via customer satisfaction lowers the elasticity of demand to price changes and improves company prestige. More recently, a study by Cheng et al (2008) has shown that RC as measured by a composite index of quantitative items (such as selling expenses and sales to major customers) has a highly significant and positive effect on market value in a sample of listed healthcare companies. In a later study, the same authors (Cheng et al, 2010) have used the input costs of maintaining customer relationship (i.e.…”
Section: Rcmentioning
confidence: 99%
“…The objective nature of the physical asset and an asset that is invisible can be achieved through the use of related assets, human resources and organizational performance relationships outside the business. All these features create value within organizations and earned value because it is a completely internal, merchantability (Chen et al, 2008). …”
Section: Intellectual Capitalmentioning
confidence: 99%